(untitled) (Editora Impacto Científico, 2025)
This study aimed to analyze the relevance of Environmental Sustainability Management in Food and Nutrition Units (FNUs) under the Worker’s Food Program (PAT), focusing on the menu’s strategic role. The PAT, as an occupational health policy, requires a menu that actively mitigates nutritional risks (overweight and NCDs) and promotes productivity. The methodology was based on a critical literature review of the PAT, corporate sustainability, and the nutritionist’s role. Results indicate that the sustainable menu is a Corporate Social Responsibility (ESG) asset, demanding resource optimization and waste reduction. The Nutritionist is the transforming agent, responsible for balancing industrial efficiency with socio-environmental quality and worker health. It is concluded that the sustainable menu within the PAT elevates the food service to a strategic investment in human capital and corporate image. DOI: https://doi.org/10.56238/edimpacto2025.090-036